Clinico-Pathological Spectrum of Prostatic Carcinoma in a Tertiary Care Hospital of Lahore (Medical Forum Monthly, 2024)
Objectives: To determine the clinico-pathological characteristics of prostate cancer in a tertiary care Hospital of LahoreStudy Design: Observational / descriptive study.Place and Duration of Study: This study was conducted at the Department of Morbid Anatomy and Histopathology, University of Health Sciences, Lahore from January 2012 to December 2015.Materials and Methods: Fifty paraffin embedded blocks of prostate specimens were selected on retrospective basis. Relevant clinical profile including age, presenting complaints and clinical diagnosis were retrieved from the clinical record. The tumours were diagnosed, sub-classified and graded according to the Revised Gleason’s score 2013.Results: Mean age of the patients was 70+22.3 years with a peak seen at65-75 years. Prostatic adenocarcinoma was diagnosed in all cases where in 75% cases it was clinically evident while in rest of the cases it was an incidental finding. Mean serum Prostatic Specific Antigen level was 98 + 11ng/d. Histologically most of the carcinomas (61%) were of large acinar type. Variable Gleason scores (GSs) were obtained and most of the carcinomas scored 7 (4+3 in 41% while 3+4 in 23% cases).Conclusion: Late presentation and lack of awareness for screening of prostatic carcinoma leads to presentation of patients in higher grade in our population